a Implementasi Database NoSQL Berbasis Cloud pada Sistem Informasi Geografis Bantuan Dana Desa Kabupaten Deli Serdang - Suendri, Suendri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
The purpose of this study is to implement the use of NoSQL cloud based database in the design of geographical information systems for the distribution of Bantuan Dana Desa disbursed by the government of the Republic of Indonesia, which is currently not owned by the Deli Serdang District Government, so that the distribution of Bantuan Dana Desa cannot be accessed by the wide community. The research method used is Research and Development (R&D) through the stages of Information Collection, System Design, System Validation, System Repair and Production Systems. This study produced a geographic information system to map the distribution of Bantuan Dana Desa in the Deli Serdang district by implementing a NoSQL cloud based non-relational database. Through this research, it can be concluded that NoSQL cloud based database is able to become one of the data storage solutions in the geographical information system of Bantuan Dana Desa in Deli Serdang district, the database using NoSQL has high flexibility, scalability because the data is stored in large amounts and continues to grow every year as long as the policy on Bantuan Dana Desa continues and has a High Performance compared to other relational databases.